How Religious Violence Ends - Juergensmeyer, Mark (Perspectives on terrorism, 2022)
This study of how three religion-related militant movements came to an end—ISIS in Iraq and Syria, Moros in Mindanao in the Philippines, and Khalistan in India’s Punjab—reveals that such movements are most decisively destroyed from within. External military force can limit and weaken a movement and provide the coup de grace that destroys it, but most movements have been dead before they were destroyed. Conversations with former activists in the three movements studied reveal that there are several factors for their implosion: infighting, a loss of faith in the goals and ideology of a movement, and the opportunities for nonviolent alternatives. Authorities resisting a violent movement can hasten the end by providing more options to violent struggle.